Inevitable Trends and Technologies of Libraries and Information Science (LIS TODAY, 2021)
This paper attempts to describe brief outline about latest trends, tools and technologies which are  being started used in management and service areas of libraries. The emergence of ICT and its effect and impact via new technologies in libraries can be understood after going through this paper. The paper tries to pick such technologies which are becoming very famous among library and information  science professionals due to its positive potential to implement and use it in LIS field. This paper tries  to show how computer, mobile, internet and related technologies have capacity to go deep inside of  library and information sector and having excellent power to manage libraries, library resources and  can serve its users.
Keywords: ICT; RFID; Cloud Computing; RDA; Library Technologies; Big Data; AI; Expert System